Just environmental business - Rolston, Holmes, 1932-2025, author; Random House, publisher (Colorado State University. Libraries, 1984)
Business and a humanistic environmental ethic, with ten maxims, such as the stakeholder maxim or the no-discount maxim. Business and a naturalistic environmental ethic, with ten maxims, such as the reversibility maxim, or the china-shop maxim. Ethical complexities in business and environmental concerns, with ten maxims, such as the buck-stopping maxim, or the burden-of-proof maxim.
Keywords: steady state; burden of proof; questioning authority; business; environment; ethical maxims; stakeholders; discounting; toxics